OXIDATIVE STRESS: ITS ROLE IN INSULIN SECRETION, HORMONE RECEPTION BY ADIPOCYTES AND LIPOLYSIS IN ADIPOSE TISSUE - V. V. Ivanov; Ye. V. Shakhristova; Ye. A. Stepovaya; O. L. Nosareva; T. S. Fyodorova; N. V. Ryazantseva; V. V. Novitsky (Бюллетень сибирской медицины, 2014)
Oxidative stress is one of the pathogenetic components of many diseases during which generation of reactive oxigen species increases and the capacity of the antioxidant protection system diminishes. In the research of the last decades special attention has been given to adipose tissue, production of adipokines by it and their role in development of immunoresistance associated with formation of the metabolic syndrome and diabetes.Search for methods of therapeutic correction of adipokine secretion disorders, their influence on metabolism of separate cells and the organism on the whole as well as development of new approaches to correction of disorders in cell sensitivity to insulin are extremely topical nowadays. Systematization and consolidation of accumulated data allow to determine the strategies of further research more accurately; as a result, we have attempted to summarize and analyze the accumulated data on the role of adipose tissue in oxidative stress development.On the basis of literature data and the results of the personal investigations, the role of adipose tissue in forming oxidative stress in diabetes has been analyzed in the article. Brief description of adipose tissue was given as a secretory organ regulating metabolic processes in adipocytes and influencing functions of various organs and systems of the body. Mechanisms of disorder in insulin secretion as well as development of insulin sesistance in type I diabetes were described along with the contribution of lipolysis in adipose tissue to these processes.